OPTIMASI KOMBINASI COCOA BUTTER DAN MILK BUTTER SEBAGAI BASIS BODY BUTTER EKSTRAK ETANOL DAUN JAMBU BIJI (Psidium guajava Linn) - Suradnyana, I Gede Made; Mahardika, I Komang Gede; Siada, Nyoman Budiartha (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Guava leaf extract is known to contain flavonoids, a class of flavone compounds that have very strong antioxidant activity. The antioxidant activity of guava leaf ethanol extract as measured by the DPPH method showed an IC50 value of 72 µg/ml. Body butter preparations have a better ability to nourish and maintain skin moisture because they contain high oil components. Cocoa butter and milk butter are the bases that are widely used in body butter formulas and are able to maintain skin health. This study aims to determine the area of optimum composition of the combination of cocoa butter and milk butter in body butter preparations of guava leaf ethanol extract (Psidium guajava L.). This study used a factorial design with two factors, namely cocoa butter and milk butter and two levels, namely 2% and 4% for cocoa butter and 2% and 15% for milk butter. The observed responses were pH and spreadibility with data analysis using Design Expert and SPSS software. Based on the results of the research, the optimum area for the combination of cocoa butter and milk butter with the pH equation is Y = 6.00000 – 1.77504(X1) – 4.73345 (X2) + 1.8336(X1X2) and the dispersion equation is Y = 3 ,77692+0,366667(X1) – 0,005128(X2) + 0.033333(X1X2). The optimal composition area of cocoa butter and milk butter has been validated on the combination of 3% cocoa butter and 8,5% milk butter.